Tamper Localization and Recovery Medical Image Watermarking: A Review - Badshah, Gran; Liew, Siau-Chuin; Jasni, Mohamad Zain; Herawan, Tutut (Universiti Malaysia Pahang, 2012)
Digital imaging technology development has improved the health care system, particularly improving digital medical imaging system used in the patient diagnoses, treatment and surgery. The remote access of digital medical images is also known as teleradiology, is an important unit of modern electronic health (eHealth) care system. Teleradiology is facing secrecy, fraud, misuses and security problems which encourage unauthorized users for copying, distributing and tampering images. Image tampering is one of the serious issues in hospital information system (HIS) based on online radiology information system (RIS) and picture archive and communication system (PACS). Medical decisions made on the basis of tampered images while diagnosing a patient can cause a non-recoverable loss. Watermarking technique is one of the best solutions to overcome this problem to locate and recover the tempered image in its original version before making any decision. This paper presents a survey of available important literature on digital image watermarking.